1995
DOI: 10.1001/archinte.1995.00430070088011
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Sleep Disturbance

Abstract: Individuals with sleep complaints should be queried about tobacco use. Those who are smokers should be advised that there is a relationship between cigarette smoking and sleep disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(50 citation statements)
references
References 12 publications
6
43
1
Order By: Relevance
“…Consistent with previous studies, active smoking was associated with insufficient rest/sleep in the current study (14;17;21;27). Effect of smokeless tobacco on sleep has not been studied before.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies, active smoking was associated with insufficient rest/sleep in the current study (14;17;21;27). Effect of smokeless tobacco on sleep has not been studied before.…”
Section: Discussionsupporting
confidence: 93%
“…Data from the 2008 Behavioral Risk Factor Surveillance System (BRFSS) showed that 11% of Americans reported insufficient rest/sleep for the preceding 30 days (12). Cigarette smoking has been shown to be associated with a range of sleep disorders including shorter sleep duration (13), difficulty initiating and maintaining sleep (14;15), snoring (16) and daytime sleepiness (17). Previous cross-sectional studies have reported associations between active cigarette smoking and insufficient rest/sleep (18) (19).…”
mentioning
confidence: 99%
“…Indeed, smokers have difficulties in initiating sleep, 54 which agrees with the lack of involuntary sleep in the present study. However, the same, and other 43 studies, also report higher sleepiness in smokers.…”
Section: Discussionsupporting
confidence: 90%
“…There is a strong negative association between smoking and sleep duration [36]. Smokers have longer sleep latency and lighter sleep [37,38]. Additionally, smokers had more daytime sleepiness, minor accidents and depression, and high daily caffeine intake [37].…”
Section: Discussionmentioning
confidence: 99%